Melatonin activates cell death programs for the suppression of uterine leiomyoma cell proliferation. Issue 1 (28th November 2019) - Lin, Po‐Han; Tung, Yen‐Ting; Chen, Hsin‐Yuan; Chiang, Yi‐Fen; Hong, Hui‐Chih; Huang, Ko‐Chieh; Hsu, Sung‐Po; Huang, Tsui‐Chin; Hsia, Shih‐Min
Abstract: The circadian nature of melatonin has a protective effect on the progression of female reproductive cancers, including breast and ovarian cancers. However, the effect of melatonin on the growth of uterine leiomyoma is still unclear. In this study, we found that the growth of uterine leiomyoma ELT3 cells was reduced by treatment with melatonin. Treatment with melatonin increased the distribution of sub‐G1 phase and increased DNA condensation in ELT3 cells. Melatonin‐induced apoptosis and autophagy cell death progression were observed in ELT3 cells. Melatonin exerts a highly selective effect on primary normal human uterine smooth muscle (UtSMC) cells. The UtSMC cell cycle was arrested by melatonin treatment through up‐regulation of p21, p27, and PTEN protein expression, but melatonin did not further promote apoptosis program activation. Melatonin reduced cell proliferation in ELT3 cells underlying the activation of melatonin MT1 and MT2 receptors, which in turn down‐regulated the Akt‐ERK1/2‐NFκB signaling pathway. Melatonin reduced ELT3 tumor growth in both xenograft and orthotopic uterine tumor mice models. The extracellular matrix of the tumor was also reduced by melatonin treatment. Taken together, these results suggest that melatonin potentially plays a role in suppression of uterine leiomyoma growth.